A comparative study of postpartum intrauterine contraceptive device acceptance between vaginal delivery and caesarean delivery of women in a 2nd tire Government hospital in West Bengal, India - Biswas, Chandralekha; Biswas, Banya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: About third fourth of the world’s population lines in the developing countries. Indian population contributes 17.7% of world population. Family planning is key factor for declining the population. It is related to every phase of maternity cycle i.e., antenatal, intranatal, postnatal or postpartum. IUCD is one the most effective reversible contraceptive method in family planning program. Methods: It was comparative study conducted over a period of two years at Gynae & Obstetrics department in a second-tier hospital in WB in India. Total 984 women had PPIUCD insertion immediately after delivery of placenta in vaginal (group A) and caesarean section (group B) after applying inclusion and exclusion criteria. All women are counseled who delivered at this hospital over the mentioned period, were included in this study. Medical eligibility criteria were used for selection. Results: Around 50% of total delivery in both groups were accepted PPIUCD. There are 68% approximately women accepted PPIUCD who delivered virginally. In primiparous women acceptance of PPIUCD was 45.5%. Acceptance of postpartum intrauterine contraceptive device was significantly higher in multipara (40.8%) who delivered vaginally. Conclusions: Acceptance of PPIUCD was significantly higher in women who delivered vaginally than cesarean section in both primiparous and multiparous women. Most common cause behind this acceptance was family planning counselling and awareness program.